Active site directed chemical modification of alpha-galactosidase from bacillus stearothermophilus (NCIM 5146): involvement of lysine, tryptophan and carboxylate residues in catalytic site - Gote, M. M.; Khan, Mohammad Islam; Khire, Jayant Malhar (Enzyme and Microbial Technology, 2007)
The catalytic amino acid residues of the extracellular a-galactosidase (alpha-D-galactoside galactohydrolase; EC 3.2.1.22) from Bacillus stearothermophilus NCIM 5146 were investigated by pH dependence and chemical modification studies. These results suggested that carboxylate and a lysine residue take part in catalysis and only lysine residues were essential for substrate binding. Carbodiimide mediated chemical modification of the enzyme also supported that a carboxylate residue located in the active site act as a nucleophile base in substrate cleavage. Acylation and reductive methylation of lysine residues by acetic, citraconic anhydride and sodium borohydride suggested that four protonated lysine residues carrying positive charge on its epsilon-amino group provides the positive charge density for binding of the substrate. Additionally four tryptophan residues also found near to the active site and in a moderately hydrophobic environment. Kinetic and thermal inactivation study of modified enzyme indicated that these tryptophan residues might have a role in the catalytic site as well as in the thermal stabilization of active site conformation at higher temperature. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Active site; alpha-galactosidase; Bacillus stearothermophilus; carboxylate; Chemical modification; lysine; Tryptophan

All-solid-state' electrochemistry of a protein-confined polymer electrolyte film - Parthasarathy, Meera; Pillai, Vijayamohanan K.; Mulla, Imtiaz S.; Shabab, Mohammed; Khan, Mohammad Islam (Biochemical and Biophysical Research Communications, 2007)
Interfacial redox behavior of a heme protein (hemoglobin) confined in a solid polymer electrolyte membrane, Nafion (a perfluoro sulfonic acid ionomer) is investigated using a unique `all-solid-state' electrochemical methodology. The supple phase-separated structure of the polymer electrolyte membrane, with hydrophilic pools containing solvated protons and water molecules, is found to preserve the incorporated protein in its active form even in the solid-state, using UV-visible, Fluorescence (of Tryptophan and Tyrosine residues) and DRIFT (diffuse reflectance infrared Fourier transform) spectroscopy. More specifically, solid-state cyclic voltammetry and electrochemical impedance of the protein-incorporated polymer films reveal that the Fe2+-form of the entrapped protein is found to bind molecular oxygen more strongly than the native protein. In the `all-solid-state' methodology, as there is no need to dip the protein-modified electrode in a liquid electrolyte (like the conventional electrochemical methods), it offers an easier means to study a number of proteins in a variety of polymer matrices (even biomimetic assemblies). In addition, the results of the present investigation could find interesting application in a variety of research disciplines, in addition to its fundamental scientific interest, including protein biotechnology, pharmaceutical and biomimetic chemistry. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: all-solid-state; cyclic voltammetry; hemoglobin; Impedance; Nafion; redox behavior

Antibacterial activity of synthesized 2,4,5-trisubstituted imidazole derivatives - Khan, Mohd Sajid; Siddiqui, Shafi Ahmad; Siddiqui, Mohammad Shaik Rafi Ahmad; Goswami, Usha; Srinivasan, Kumar Venkatraman; Khan, Mohammad Islam (Chemical Biology & Drug Design, 2008)
Some novel chemically synthesized 2,4,5-trisubstituted imidazoles from aryl aldehydes and 1,2-diketones or alpha-hydroxyketone were screened against eight different human pathogenic bacteria and fungi. Seven compounds were found to be active against different bacteria. These compounds showed variation in activity and were found to be active against Gram-positive as well as Gram-negative bacteria. Compound 4-(4,5-diphenyl-1H-imidazol-2-yl)-phenol, 3d was the only compound which showed activity against Klebsiella pneumoniae while rest of the compounds did not show significant activity against this micro-organism. Minimum inhibitory concentrations of the compounds were in the range of 0.50 to 6.1 mu g/mL and minimum bactericidal concentration ranges from 1.11 to 12.9 mu g/mL. The candidature of active compounds to be an effective and novel drug was examined based on Lipinski's rule of Five which explained ClogP, LogS, H-bond acceptors, H-Bond donors and rotational bonds. Compounds 3a-d and 3f satisfies Lipinski's rule of Five and could be proposed as potent new antibacterial drugs.
Keywords: 1; 2; 2-Diketones; 4; 5-trisubstituted imidazoles; alpha-hydroxyketone; antibacterial activity; aryl aldehydes